Nanocondensate bioadhesive delivery via metal–halogenated catechol coordination in tunicate rhizoid holdfasts - Hyungbin Kim; Seunghyeon Lee; Samantha Jee; Geonho Song; Dorian Schoenaers; Jérôme Delroisse; Patrick Flammang; Matthew J. Harrington; Dong Soo Hwang (Proceedings of the National Academy of Sciences, 2026)
The root-like holdfast of the tunicate Halocynthia roretzi provides strong underwater adhesion. However, the biological processing and biochemical composition underlying its adhesive remain largely unknown. Here, we identify a nanocondensate-based transport system in which halogenated 3,4-dihydroxyphenylalanine (DOPA)-containing peptides coordinate with metal ions such as iron, chromium, and vanadium to form stable nanocondensates within dense-granular cells. These nanocondensates are secreted into the extracellular matrix and rapidly incorporated into the cuticular layer, where the proteins cross-link oxidatively to form the adhesive interface, releasing the metals upon solidification. This process establishes a previously unrecognized solid-state adhesive delivery mechanism regulated by coordination chemistry between metal ions and halogenated catechols. Indeed, while other systems (e.g., mussels) use DOPA-containing proteins to transport metal ions during glue formation, the current system is distinctive in that metal coordination is transient and used ostensibly to deliver the adhesive protein cargo—findings relevant for design of next-generation underwater glues.